Evaluation of Wound Healing Activity of Catharanthus Roseus Aqueous Extract in Adult Albino Rats: Pharmaceutical Sciences-Medicine for novel therapy - Satish, A M; M. K, Jayanthi; Gangadhar, Totagi Vinod; Ramu, Ramith (International Journal of Life Science and Pharma Research, 2021)
Use of plant extracts in the treatment of several ailments is a science known to the mankind since time immemorial. Yet, its popularity is limited owing to the lack of recorded experimental evidence to determine their potential health benefits. C. roseus is a traditional medicinal plant with over 100 identified alkaloids and several other phytochemicals known for various health promoting activities. The aim of the present study was to evaluate C. roseus aqueous extracts’ wound healing potential using incision, excision, and dead space wound models on healthy male albino rats. To assess this, the tissue breaking strength for incision wound model, percent epithelialization and period to complete epithelialization for excision wound model and granuloma break strength, dry weight, and hydroxyproline content for dead space wound model were evaluated after the treatment of the extract in comparison with the standard drug sucralfate. The results obtained demonstrated that the treatment of extract on the wound significantly enhanced tissue breaking strength and reduced the time required for complete epithelialization and was on par with that of the standard drug sucralfate. In the incision wound model, an elevated breaking strength was observed compared to that of the control group. Further, in the dead space wound model, the granuloma dry weight and breaking strength were remarkably elevated along with a concomitant increase in the hydroxyproline content suggesting the enhanced rate of wound contraction rate, collagen synthesis and lowered healing period. In conclusion, the present study demonstrates that C. roseus is effective in wound healing, as shown in the three wound models and thus, further studies to formulate this into a commercial product should be carried out.